ANALISIS RENTABILITAS PADA INDUSTRI PERHOTELAN YANG TERDAFTAR DI BURSA EFEK INDONESIA - Akandji, Vidya; Tinangon, Jantje J.; Pontoh, Winston (Universitas Sam Ratulangi, 2020)
As business increasingly global, financial statements are more important than ever before. As a basis of competitive analysis, credit decisions, business negotiation and legal entity control. For investor or potential investor, it would be better to analyse the company’s financial performace first. In assessing the company’s financial performance, one of the indicators that mostly used is accounting investment in the form of a company’s financial satatement. This study was conducted in the hospitality industry listed on the stock exchange with aim to analyse financial statement in assessing the company’s financial performance. The analytical method used in this study is a quantitative analysis method. From the financial statement there is an analysis of profitability to be able to predict the condition of the company’s in the future. The results of profitability ratio which consist of profit margin, gross profit margin, net profit margin, ROI, and ROA show that ability of the company to get profits from all sources have varies performances. There are companies which have good, standard and poor performances.